Ill-structured on respiratory system: How does the contextual problem improve students’ problem-solving skills by developing electronic worksheet? - Martiana Dayani Tambunan; Z. Zulfiani; Eny Supriyati Rosyidatun (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
This research aims to develop an electronic student worksheet based on respiratory problem to improve problem-solving skills on the respiratory system concept. This research and development (R&D) using 4D model proposed by Thiagarajan consist of define, design, develop, and disseminate. E-worksheets were validated by three experts, i.e. the material experts, media experts, and biology teacher as a practitioner. The result of the research showed that the e-worksheet developed had an average validity percentage of 81.85% with a very good category. While the e-worksheet readability was 96.67% (very good). Furthermore, either the teacher or students shows that the field trial test of the e-worksheet had good criteria due to their responses of 94.58% and 88.39%, respectively. The research results shows that there is an increase on students’ problem-solving skills based on the N-gain score of 0.47 and classified as medium category. Based on these results, it can be concluded that e-worksheet is very suitable for use in learning activities and can improve student’s problem-solving skills.